Au@TiO2–CdS ternary nanostructures for efficient visible-light-driven hydrogen generation - Yin, Li-Sha (2013)
We report a new type of Au@TiO2-CdS ternary nanostructures by decorating CdS nanoparticles onto Au@TiO2 core-shell structures. Comparing to the binary structures, such as CdS-TiO2 and Au@TiO2, these ternary nanostructures exhibit remarkably high photocatalytic H2 generation rate under visible-light irradiation. The enhanced photocatalytic activity is attributed to the unique ternary design, which builds up a transfer path for the photoexcited electrons of CdS to the core Au particles via the TiO2 nanocrystal bridge, and thus effectively suppressed the electron-hole recombination on the CdS photocatalyst. This internal electron transfer pathway (CdS→TiO2→Au) eliminates the needs of post-deposition of metal co-catalyst since the core Au nanoparticle can act as the interior active catalyst for proton reduction towards hydrogen evolution. We believe that our work demonstrates a promising way for rational design of metal-semiconductor hybrid photocatalysts to achieve high photocatalytic efficiency for solar fuels production.